EVALUATION OF THE FEATURES OF THE DISTRIBUTION OF THE MAXIMUM RUNOFF OF SPRING FLOODS UNDER THE PRESENT CONDITIONS OF CLIMATE CHANGE IN THE MARMARIK RIVER BASIN (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The paper considers the patterns of distribution of long-term extreme maximum flows of spring floods in different river sections of the rivers of the Marmarik basin in the context of expected climate change and gives a quantitative assessment of these changes. Issues of changing cyclicity and synchronism, normalized deviation of the maximum runoff values are discussed. The actual observational data of the "Center for Hydrometeorology and Monitoring" of the SNCO of the Ministry of Environment of the Republic of Armenia are used. On the Marmarik River downstream, the values of the absolute maximum discharges increase and reach high values in the closing river section of Aghavnadzor. The highest maximum discharge observed on April 18, 1968 in the alignment of the settlement of Aghavnadzor was 86.7 m3/s. In Marmarik River basin a regular decrease in the maximum runoff modules during the flood period with an increase in catchment areas was also observed. With an increase in the areas of watersheds, the maximum runoff modulus decreases – from 370–450 L/s·km2 in areas less than 90–100 km2 and less than 200 L/s·km2 in areas more than 400 km2. A correlation was found between the values of absolute maximum discharges increase during the period of high water on Marmarik River in the village of Agavnadzor and on Gomraget River in Meghradzor settlement, which can be used for calculations and forecasts of spring flood runoff maxima. An almost twofold decrease in the magnitude of the extreme maximum runoff of spring floods (negative trend) in the modern period was revealed. An analysis of the causes of the identified changes was carried out.
Keywords: extreme maximum flow; cyclicity and synchronism; normalized deviation of maximum flow; long-term fluctuations; trend; Marmarik River basin